2016
DOI: 10.1186/s12885-016-2962-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor characteristics and prognosis in familial breast cancer

Abstract: BackgroundApproximately 5–10% of breast cancers are hereditary and their biology and prognosis appear to differ from those of sporadic breast cancers. In this study we compared the biological features and clinical characteristics of non metastatic breast cancer in patients with BRCA mutations versus patients with a family history suggesting hereditary breast cancer but without BRCA mutations (BRCA wild type) versus patients with sporadic disease, and correlated these findings with clinical outcome.MethodsWe re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
2
16
1
1
Order By: Relevance
“…As regard tumor size; the present study showed a significantly higher percentage of T4 tumors in patients with positive family history. This disagrees with Arpino et al (25) who found no significant relation between tumor size and familial or sporadic breast cancer. Also, this study reported that bilateral breast cancer was significantly more frequently in the FBC group.…”
Section: Resultscontrasting
confidence: 96%
“…As regard tumor size; the present study showed a significantly higher percentage of T4 tumors in patients with positive family history. This disagrees with Arpino et al (25) who found no significant relation between tumor size and familial or sporadic breast cancer. Also, this study reported that bilateral breast cancer was significantly more frequently in the FBC group.…”
Section: Resultscontrasting
confidence: 96%
“…The type of surgery performed differs significantly, where female with BRCA mutation more often choose mastectomy, a decision made together with their physician. Risk of recurrence and risk of contralateral breast cancer is the same in genetically caused breast cancer with and without BRCA mutation and it is greater than the risk in sporadic cancers [ 29 ].…”
Section: Individuals With Increased Risk Of Breast Cancermentioning
confidence: 99%
“…Thirty‐four patients, selected as previously described, and four cell lines, as positive controls, were analyzed in this study. With the aim of identifying gene sequence variations in BC samples from patients with and without BRCA gene mutations, we designed a multigene custom panel including 27 genes specifically involved in DNA damage repair pathways; 50 ng of input DNA was used for library preparation and sequencing as detailed in Material and methods.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four patients, selected as previously described, 17 Globally, the designed test led to the identification of about 40 gene sequence variations, as detailed in Table S2, most of them being already described as BC predisposing ones, including all those previously identified in the same patients by Sanger sequencing of BRCA1 and BRCA2. In particular, we first evaluated sequence quality at the BRCA loci, finding 15 known variations in different patients.…”
Section: Re Sultsmentioning
confidence: 99%